Morphology and Magnetic Properties of Hexagonal Ferrite Sr₁₋ₓMₓFe₁₂₋ₓZnxO₁₉ (M= La, Dy, Nd, Yb) - Mohd Saiden, Norlaily (2003)
A permanent magnet in the form of a ring or disc is one of the components in many devices. In this project, hard magnetic ferrite with formula Sr₁₋ₓMₓFe₁₂₋ₓZnxO₁₉ (x= 0.1, 0.3, 0.5, 0.7, 0.9) (M= La, Nd, Dy, Vb) is used because of the low cost, high energy, good electrical insulation, hard to demagnetize and easy to process. Substitutions from Lanthanide group and zinc oxide (non magnetic material) are used in order to get different microstructures according to the value of hysteresis properties. Hysteresis parameters are investigated such as the remanence, Br, energy product (BH)max and coercive force He Conventional sintering technique is used with sample being formed in disc shape. From XRD result, it was found that the substitution of Yb₂O₃,Nd₂O₃,La₂O₃,Dy₂O₃ and ZnO to the strontium ferrite magnet stabilizes the magnetoplumbite phase. The results for density, Curie temperature and grain size are better than non-substituted Sr-M. As a conclusion, improvement of the magnetic properties has been done to produce high performance of Sr-M in the future.